2009
DOI: 10.1007/s11356-009-0100-1
|View full text |Cite
|
Sign up to set email alerts
|

Trihalomethane formation during water disinfection in four water supplies in the Somes river basin in Romania

Abstract: Background, aim and scope After the discovery of chloroform in drinking water, an extensive amount of work has been dedicated to the factors influencing the formation of halogenated disinfections by-products (DBPs). The disinfection practice can vary significantly from one country to another. Whereas no disinfectant is added to many water supplies in Switzerland or no disinfectant residual is maintained in the distribution system, high disinfectant doses are applied together with high residual concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Zaharie Moldovan (National Institute for Isotopic and Molecular Technology, Cluj-Napoca, Romania) and Dumitru Ristoiu (University Babes-Bolyai, Cluj-Napoca, Romania) reported on the ESTROM projects PHARMSOMES (Moldovan and Alder 2009) and WAQUA (Ristoiu et al 2009), respectively. A topic lecture was presented by Frajo Wirtz (IAWR, International Association of Waterworks in the Rhine catchment area) presenting the "Danube, Meuse and Rhine MEMORANDUM 2008".…”
Section: The Biological and Hydromorphological Dimension Of The Eu Wfmentioning
confidence: 99%
“…Zaharie Moldovan (National Institute for Isotopic and Molecular Technology, Cluj-Napoca, Romania) and Dumitru Ristoiu (University Babes-Bolyai, Cluj-Napoca, Romania) reported on the ESTROM projects PHARMSOMES (Moldovan and Alder 2009) and WAQUA (Ristoiu et al 2009), respectively. A topic lecture was presented by Frajo Wirtz (IAWR, International Association of Waterworks in the Rhine catchment area) presenting the "Danube, Meuse and Rhine MEMORANDUM 2008".…”
Section: The Biological and Hydromorphological Dimension Of The Eu Wfmentioning
confidence: 99%
“…Recently, trihalomethanes, which have generated serious concerns about the safety of tap water, have been shown to be carcinogenic substances [6,7]. They are formed during the process of chlorine sterilization and disinfection processing by reactions with organic compounds, for example, dyestuff or humic acid in nature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…They are formed during the process of chlorine sterilization and disinfection processing by reactions with organic compounds, for example, dyestuff or humic acid in nature [7][8][9]. The wastewater in the textile industry contains not only hazardous materials but also a high concentration of dyestuff and nitrogenous substances.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine, which exists as hypochlorous acid and hypochlorite in water, reacts with natural DOM, such as humic and fulvic acids to form THMs (Gallard and von Gunten 2002;Ristoiu et al 2009). In the presence of bromides in source waters, hypobromous acid is formed when chlorine is used as disinfectant (Westerhoff et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that THMs suspect to cause liver and kidney damage, retarded fetus growth, birth defects, and possibly miscarriage (Wright et al 2004;Ristoiu et al 2009). The rapid growth of Delhi, due to the growing influx of population into the urban city from the neighboring states and also from the other parts of the country, has resulted in significant increase in drinking water demand.…”
Section: Introductionmentioning
confidence: 99%